Advances in Audio Watermarking Based on Matrix Decomposition - Dhar, Pranab Kumar; Shimamura, Tetsuya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces audio watermarking methods in transform domain based on matrix decomposition for copyright protection. Chapter 1 discusses the application and properties of digital watermarking. Chapter 2 proposes a blind lifting wavelet transform (LWT) based watermarking method using fast Walsh Hadamard transform (FWHT) and singular value decomposition (SVD) for audio copyright protection. Chapter 3 presents a blind audio watermarking method based on LWT and QR decomposition (QRD) for audio copyright protection. Chapter 4 introduces an audio watermarking algorithm based on FWHT and LU decomposition (LUD). Chapter 5 proposes an audio watermarking method based on LWT and Schur decomposition (SD). Chapter 6 explains in details on the challenges and future trends of audio watermarking in various application areas. Introduces audio watermarking methods for copyright protection and ownership protection; Describes watermarking methods with encryption and decryption that provide excellent performance in terms of imperceptibility, robustness, and data payload; Discusses in details on the challenges and future research direction of audio watermarking in various application areas.
Chapter1: Introduction -- Chapter2: LWT-Based Audio Watermarking Using FWHT and SVD -- Chapter3: Audio Watermarking Based on LWT and QRD -- Chapter4: Audio Watermarking Based on FWHT and LUD -- Chapter5: Audio Watermarking Based on LWT and SD -- Chapter6: Conclusions and Future Work.
Keywords: Signal processing; Computational linguistics; Algorithms; Signal, Speech and Image Processing; Computational Linguistics; Algorithms